IMPROVING THE TECHNOLOGY OF PURIFICATION OF NATURAL AND SECONDARY GASES FROM SULFUR COMPOUNDS - Aripdjanov Oybek Yusupdjanovich; Kholmatov Shokhrukh Furqat ugli; Kayumov Jamshid Sayfullayevich (Galaxy International Interdisciplinary Research Journal, 2023)
Natural, organomineral, synthetic and composite sorbents are used to clean oil and gas from sour gases, the production of which is increasing year after year. Approximately 55% of which are used to purify natural and industrial gases from sulfur-containing organic compounds, mercaptans, carbonyl sulfide, carbon disulfide and other sulfur-containing compounds. At the same time, special attention is paid to the production of a new composite universal generation of these sorbents and technologies for their extraction and use.